Analisis Kemampuan Retensi Panas Pada Berbagai Merek Tumbler (Botol Insulasi) Berdasarkan Hukum Pendinginan Newton - Raditya bayu herlambang; Muhamad Safi’i; Althesa Androva (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2026)
Tumblers or insulated bottles are everyday consumer products designed to maintain beverage temperature over a period of time. This study aims to analyze the heat retention capability of five commercial tumbler brands Zojirushi SX-CC45, Hydro Flask 32oz, Stanley Classic, Thermos Stainless, and Generic Brand A using a quantitative approach based on Newton's Law of Cooling. Hot water at an initial temperature of 90°C was poured into each tumbler, and temperature was measured every 10 minutes for 120 minutes at an ambient temperature of 28°C. The total heat decay coefficient (k) was obtained through nonlinear regression to the exponential model Tt= Tamb + (T₀ − T amb)e⁻kt. Results indicate k values ranging from 0.0021 min⁻¹ (Zojirushi, best) to 0.0127 min⁻¹ (Generic Brand A, worst), with heat retention efficiency at 120 minutes of 85.3% and 20.8%, respectively. R² values for all fitting curves exceed 0.99, confirming the validity of Newton's model in a closed system. This study provides a quantitative reference for consumers in selecting quality tumblers and a scientific basis for manufacturers to improve product insulation design.